Pengaruh Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Bank Rakyat Indonesia Cabang Putri Hijau Medan - Mutia Arda (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The purpose of this study is to analyze the effect of job satisfaction and employee discipline on the work performance of Bank Rakyat Indonesia Branch Putri Hijau Medan. This type of research is associative. The population of this research is all employees in a marketing department of Bank Rakyat Indonesia Branch Putri Hijau Medan as many as 31 employees and all become sample. This research uses census method or saturated sample. Methods of data collection of this study are questionnaires, interviews, and documentation. Methods of data analysis using descriptive analysis and multiple linear regression. The results of this study indicate that job satisfaction has a positive and insignificant effect on employee performance, Discipline has the positive and significant influence on performance, while simultaneously job satisfaction and work discipline together positively influence to employee performance of Bank Rakyat Indonesia Branch of Putri Hijau Medan. Employee discipline has a dominant influence on job satisfaction. The coefficient of determination (Adjusted R Square) is 0.162 means that 16.2% performance variables can be explained from job satisfaction and employee discipline while as much as 83.8% can be explained by other variables which are not examined by researchers in this study.